A global climatological study of the ionospheric foF2 and hmF2 covariance - Danielle Edwards; Manuel Cervera; Bruce Ward; Andrew MacKinnon (Advances in Space Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Increasing meatless options to decrease meat consumption - a quantitative analysis of the relationship between the percentage of meatless items offered on a specials menu and meatless purchases - Danielle Mary Edwards; Peter Ondish; Roni Neff (Food Quality and Preference, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Regional conservation genomics: insights and opportunities from northern Australia - Teigan Cremona; Brenton von Takach; Robyn Shaw; Alexander Carey; Bridget Campbell; Skye Cameron; Renee Catullo; Caroline Chong; Saul Cowen; Danielle Edwards; Emilie Ens; Tony Griffiths; et al. (Biodiversity and Conservation, 2025)
Biodiversity conservation in northern Australia is characterised by high endemism, data deficiency, and high Indigenous land tenure and population. The Northern Australia Conservation Genomics Forum brought together experts to explore current genetic research with particular emphasis on integration of genomics within conservation practices. We discuss the regional biodiversity of northern Australia, highlighting the unique biogeographic patterns, known and unknown species diversity, and ongoing threats such as habitat degradation, altered fire regimes, invasive species, and climate change. This article synthesises key themes from the forum, including the current application of genomics in conservation, gaps and areas of need and opportunity to advance species conservation in this sparsely populated, yet iconic region of Australia. We highlight the need to expand collaborative research partnerships across land tenures with Indigenous organisations, pastoralists, government and non-government organisations, which is crucial for the effective study and conservation of the region’s biodiversity. The paper identifies the challenges and opportunities in applying genomic data to conservation strategies and applied management, including species translocations and habitat management, while acknowledging the limitations and gaps in current research and collections. The insights from this forum emphasise the advantages in using genomics to inform conservation decisions, and the need for continued research and collaboration to protect northern Australia’s unique biodiversity.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

CLIMF2: A climatological model of the ionospheric F2 layer. Part 1: Model methodology - Danielle J. Edwards; Thomas E. Chambers; Manuel A. Cervera (Advances in Space Research, 2025)

CLIMF2: A climatological model of the ionospheric F2 layer. Part 2: Validation and comparison with IRI - Danielle J. Edwards; Thomas E. Chambers; Manuel A. Cervera (Advances in Space Research, 2025)

Coral reef attributes associated with microplastic exposure - Cheryl Hankins; Danielle Lasseigne; Sarah M. Davis; Kimberly Edwards; Jenny S. Paul (Coral Reefs, 2025)
Coral reef declines have been documented since the 1980’s from a variety of global and local stressors. Management resource tools are needed to preserve these fragile ecosystems from stressors, both known and unknown. Laboratory studies have shown microplastics (MP) to have negative effects on coral physiology, but their effects in a natural environment are not well understood. Thus, our primary objectives were to explore associations between MPs and coral reef attributes. We measured MP concentrations from sub-surface water and coral tissue samples from two Caribbean/Atlantic scleractinian coral species, Montastraea cavernosa and Orbicella faveolata, from St. John, U.S. Virgin Islands and Florida’s Coral Reef in 2017 and 2018, respectively. Polymer identification yielded mostly cotton or polyester fibers for both water and coral tissue samples. This study is the first to document MPs in coral tissues from either the U.S. Virgin Islands or Florida’s Coral Reef and is the first to explore how MPs relate to coral reef attributes. Significant, positive relationships were seen between MPs in coral tissue and coral density, rugosity, and percent coral cover, indicating MPs may not have immediate adverse effects on coral reef health.

Correction to: Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon‑Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)

Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon-Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)
Recent extremes of flood and drought across Australia have raised questions about the recurrence of such rare events and highlighted the importance of understanding multi-decadal climate variability. However, instrumental records over the past century are too short to adequately characterise climate variability on multi-decadal and longer timescales or robustly determine extreme event frequencies and their duration. Palaeoclimate reconstructions can provide much-needed information to help address this problem. Here, we use the 600-year hydroclimate record captured in the eastern Australian and New Zealand Drought Atlas (ANZDA) to analyse drought and pluvial frequency trends for East Australian Natural Resource Management (NRM) clusters. This partitioning of the drought atlas grid points into recognised biophysical areas (i.e. NRM clusters) revealed their differences and similarities in drought intensity and pluvial events over time. We find sustained multi-decadal periods of a wet–dry geographic 'seesaw' between eastern to central and southern NRMs (e.g. 1550–1600 CE and 1700–1750 CE). In contrast, other periods reveal spatially consistent wetting (e.g. 1500–1550 CE) or drying (e.g. 1750–1800 CE). Emerging hot spot analysis further shows that some areas that appear naturally buffered from severe drought during the instrumental period have a greater exposure risk when the longer 600-year record is considered. These findings are particularly relevant to management plans when dealing with the impacts of climate extremes developed at regional scales. Our results demonstrate that integrating and extending instrumental records with palaeoclimate datasets will become increasingly important for developing robust and locally specific extreme event frequency information for managing water resources.

Climate-smart fisheries: CO2 emissions reduction and food security are complementary - Nwamaka Okeke-Ogbuafor; Tim Gray; Sheku Kamara; Edward Sesay; Abdulai Dauda; Selina M Stead; Danielle Robinson; Kelechi Johnmary Ani (Marine Policy, 2024)

Zebrafish as a model for cardiac disease; Cryo-EM structure of native cardiac thin filaments from Danio Rerio - Marston Bradshaw; John M. Squire; Edward Morris; Georgia Atkinson; Rebecca Richardson; Jon Lees; Massimo Caputo; Giulia M. Bigotti; Danielle M. Paul (Journal of Muscle Research and Cell Motility, 2023)
Actin, tropomyosin and troponin, the proteins that comprise the contractile apparatus of the cardiac thin filament, are highly conserved across species. We have used cryo-EM to study the three-dimensional structure of the zebrafish cardiac thin and actin filaments. With 70% of human genes having an obvious zebrafish orthologue, and conservation of 85% of disease-causing genes, zebrafish are a good animal model for the study of human disease. Our structure of the zebrafish thin filament reveals the molecular interactions between the constituent proteins, showing that the fundamental organisation of the complex is the same as that reported in the human reconstituted thin filament. A reconstruction of zebrafish cardiac F-actin demonstrates no deviations from human cardiac actin over an extended length of 14 actin subunits. Modelling zebrafish homology models into our maps enabled us to compare, in detail, the similarity with human models. The structural similarities of troponin-T in particular, a region known to contain a hypertrophic cardiomyopathy ‘hotspot’, confirm the suitability of zebrafish to study these disease-causing mutations.

Integrated research in the Arctic – Ecosystem linkages and shifts in the northern Bering Sea and eastern and western Chukchi Sea - Matthew R. Baker; Edward V. Farley; Seth L. Danielson; Calvin Mordy; Kathleen M. Stafford; Danielle M.S. Dickson (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Measuring Nutrition Literacy in Breast Cancer Patients: Development of a Novel Instrument - Heather D. Gibbs; Edward F. Ellerbeck; Christie Befort; Byron Gajewski; Amy R. Kennett; Qing Yu; Danielle Christifano; Debra K. Sullivan (Journal of Cancer Education, 2016)

Lineage fusion in G alápagos giant tortoises - Ryan C. Garrick; Edgar Benavides; Michael A. Russello; Chaz Hyseni; Danielle L. Edwards; James P. Gibbs; Washington Tapia; Claudio Ciofi; Adalgisa Caccone (Molecular Ecology, 2014)
Although many classic radiations on islands are thought to be the result of repeated lineage splitting, the role of past fusion is rarely known because during these events, purebreds are rapidly replaced by a swarm of admixed individuals. Here, we capture lineage fusion in action in a Galápagos giant tortoise species, Chelonoidis becki , from Wolf Volcano (Isabela Island). The long generation time of Galápagos tortoises and dense sampling (841 individuals) of genetic and demographic data were integral in detecting and characterizing this phenomenon. In C. becki, we identified two genetically distinct, morphologically cryptic lineages. Historical reconstructions show that they colonized Wolf Volcano from Santiago Island in two temporally separated events, the first estimated to have occurred ~199 000 years ago. Following arrival of the second wave of colonists, both lineages coexisted for approximately ~53 000 years. Within that time, they began fusing back together, as microsatellite data reveal widespread introgressive hybridization. Interestingly, greater mate selectivity seems to be exhibited by purebred females of one of the lineages. Forward‐in‐time simulations predict rapid extinction of the early arriving lineage. This study provides a rare example of reticulate evolution in action and underscores the power of population genetics for understanding the past, present and future consequences of evolutionary phenomena associated with lineage fusion.

Immunohistochemical localization of urea and ammonia transporters in two confamilial fish species, the ureotelic gulf toadfish (Opsanus beta) and the ammoniotelic plainfin midshipman (Porichthys notatus) - Carol Bucking; Susan L. Edwards; Paul Tickle; Craig P. Smith; M. Danielle McDonald; Patrick J. Walsh (Cell and Tissue Research, 2013)

Phylogenetic structure of vertebrate communities across the A ustralian arid zone - Hayley C. Lanier; Danielle L. Edwards; L. Lacey Knowles (Journal of Biogeography, 2013)
Aim To understand the relative importance of ecological and historical factors in structuring terrestrial vertebrate assemblages across the A ustralian arid zone, and to contrast patterns of community phylogenetic structure at a continental scale. Location Australia. Methods We present evidence from six lineages of terrestrial vertebrates (five lizard clades and one clade of marsupial mice) that have diversified in arid and semi‐arid A ustralia across 37 biogeographical regions. Measures of within‐lineage community phylogenetic structure and species turnover were computed to examine how patterns differ across the continent and between taxonomic groups. These results were examined in relation to climatic and historical factors, which are thought to play a role in community phylogenetic structure. Analyses using a novel sliding‐window approach confirm the generality of processes structuring the assemblages of the A ustralian arid zone at different spatial scales. Results Phylogenetic structure differed greatly across taxonomic groups. Although these lineages have radiated within the same biome – the A ustralian arid zone – they exhibit markedly different community structure at the regional and local levels. Neither current climatic factors nor historical habitat stability resulted in a uniform response across communities. Rather, historical and biogeographical aspects of community composition (i.e. local lineage persistence and diversification histories) appeared to be more important in explaining the variation in phylogenetic structure. While arid‐zone assemblages show an overall tendency towards phylogenetic clustering, this pattern was less pronounced at finer spatial scales. Main conclusions By focusing within different taxonomic groups and between those groups within regions, we show that although the vertebrate lineages we examined exhibited high diversity and low turnover across the arid zone, the underlying phylogenetic structure differs between regions and taxonomic groups, suggesting that taxon‐specific histories are more important than habitat stability in determining patterns of phylogenetic community relatedness.

Phylogeographic analysis detects congruent biogeographic patterns between a woodland agamid and Australian wet tropics taxa despite disparate evolutionary trajectories - Danielle L. Edwards; Jane Melville (Journal of Biogeography, 2010)
Aim To test the congruence of phylogeographic patterns and processes between a woodland agamid lizard ( Diporiphora australis ) and well‐studied Australian wet tropics fauna. Specifically, to determine whether the biogeographic history of D. australis is more consistent with a history of vicariance, which is common in wet tropics fauna, or with a history of dispersal with expansion, which would be expected for species occupying woodland habitats that expanded with the increasingly drier conditions in eastern Australia during the Miocene–Pleistocene. Location North‐eastern Australia. Methods Field‐collected and museum tissue samples from across the entire distribution of D. australis were used to compile a comprehensive phylo‐geographic dataset based on c . 1400 bp of mitochondrial DNA (mtDNA), incorporating the ND2 protein‐coding gene. We used phylogenetic methods to assess biogeographic patterns within D. australis and relaxed molecular clock analyses were conducted to estimate divergence times. Hierarchical Shimodaira–Hasegawa tests were used to test alternative topologies representing vicariant, dispersal and mixed dispersal/vicariant biogeographic hypotheses. Phylogenetic analyses were combined with phylogeographic analyses to gain an insight into the evolutionary processes operating within D. australis . Results Phylogenetic analyses identified six major mtDNA clades within D. australis , with phylogeographic patterns closely matching those seen in many wet tropics taxa. Congruent phylogeographic breaks were observed across the Black Mountain Corridor, Burdekin and St Lawrence Gaps. Divergence amongst clades was found to decrease in a north–south direction, with a trend of increasing population expansion in the south. Main conclusions While phylogeographic patterns in D australis reflect those seen in many rain forest fauna of the wet tropics, the evolutionary processes underlying these patterns appear to be very different. Our results support a history of sequential colonization of D. australis from north to south across major biogeographic barriers from the late Miocene–Pleistocene. These patterns are most likely in response to expanding woodland habitats. Our results strengthen the data available for this iconic region in Australia by exploring the understudied woodland habitats. In addition, our study shows the importance of thorough investigations of not only the biogeographic patterns displayed by species but also the evolutionary processes underlying such patterns.

Formulation and Pharmacokinetics of Self-Assembled Rifampicin Nanoparticle Systems for Pulmonary Delivery - Jean C. Sung; Danielle J. Padilla; Lucila Garcia-Contreras; Jarod L. VerBerkmoes; David Durbin; Charles A. Peloquin; Katharina J. Elbert; Anthony J. Hickey; David A. Edwards (Pharmaceutical Research, 2009)

Climatic fluctuations shape the phylogeography of a mesic direct‐developing frog from the south‐western Australian biodiversity hotspot - Danielle L. Edwards; J. Dale Roberts; J. Scott Keogh (Journal of Biogeography, 2008)
Aim To assess phylogeographic pattern throughout the range of Metacrinia nichollsi in order to develop specific biogeographical hypotheses for the wet forests of south‐western Australia. This was carried out by contrasting a direct‐developing frog species, M. nichollsi , that breeds independently of free surface water with conventional, aquatic breeders and highly specialized direct developers. Location Wet forests of the south‐western Australian biodiversity hotspot – an area of high species richness and endemism for myobatrachid frogs and many other faunal groups. Methods We compiled an extensive phylogeographic data set from field‐collected samples based on mitochondrial ND2 sequences. Phylogenetic analyses combined with estimates of divergence times were used to build a model of major biogeographical events affecting the species. Phylogeographic analyses were used to provide insights into smaller‐scale processes acting within each major lineage. Results Phylogenetic analysis recovered three major lineages, with divergence dates coincident with late Miocene–early Pliocene arid cycles. One lineage was confined to geographically isolated populations in the Stirling Ranges (Stirling Ranges Lineage, SRL). The continuous range of M. nichollsi was split into two: the Main Range Lineage (MRL) and the Southern Coastal Lineage (SCL). The SCL displays a strong drainage‐based population structure, whereas the MRL displays a strong signature of recent expansion, suggesting that these two lineages have had very different biogeographical histories. Main conclusions Late Miocene–Pliocene aridity appears to have isolated populations in the Stirling Ranges and resulted in the formation of two additional lineages on a north–south gradient that are independent of southward‐flowing drainage systems. Our results demonstrate that climatic fluctuations are likely to have generated fine‐scale phylogeographic structure within M. nichollsi and that catchment regions are important refugia during arid cycles.

Impact of Plio‐Pleistocene arid cycling on the population history of a southwestern Australian frog - DANIELLE L. EDWARDS; J. DALE ROBERTS; J. SCOTT KEOGH (Molecular Ecology, 2007)
Southwestern Australia is regarded as a global biodiversity hotspot. The region contains a high number of endemic species, ranging from Gondwanan relicts to much more recently evolved plant and animal species. Myobatrachid frogs are diverse in southwestern Australia, and while we know they have speciated in situ in the southwest, we know little about the temporal and geographical patterning of speciation events. Crinia georgiana is an ideal subject to test hypotheses concerning the effect of climatic history on southwestern Australian anurans, as it is an old lineage with a broad distribution covering the entire region. We compiled an extensive phylogeographical data set based on 1085 bp of the mitochondrial gene ND2 for 68 individuals from 18 sites across the species’ range. Two major genetic clades were identified which were largely confined to the high rainfall and southeast coastal biogeographical zones, respectively. The clades appear to have diverged around the Plio‐Pleistocene border (1.26–1.72 million years ago), concordant with increasing intensity and frequency of arid climate cycles. Subsequent phylogeographical structure appears to have developed primarily during the Pleistocene climatic fluctuations that also have been integral in generating species diversity in the endemic southwestern Australian flora. Phylogeographical analyses identified several dispersal routes, possible refugial areas within the range of the species and also regions of secondary contact. Dispersal routes identified may now be closed to the species because of habitat destruction and salinity problems in inland regions, posing concerns about the evolutionary potential of the species in light of predicted climate change.

The Absorption of Darbepoetin Alfa Occurs Predominantly via the Lymphatics Following Subcutaneous Administration to Sheep - Danielle N. McLennan; Christopher J. H. Porter; Glenn A. Edwards; Anne C. Heatherington; Steven W. Martin; Susan A. Charman (Pharmaceutical Research, 2006)

Impairment of specific episodic memory processes by sub-psychotic doses of ketamine: the effects of levels of processing at encoding and of the subsequent retrieval task - Garry D. Honey; Rebekah A. E. Honey; Sam R. Sharar; Danielle C. Turner; Edith Pomarol-Clotet; Dharshan Kumaran; Jon S. Simons; Xiangen Hu; Michael D. Rugg; Edward T. Bullmore; Paul C. Fletcher (Psychopharmacology, 2005)

Pharmacokinetic Model to Describe the Lymphatic Absorption of r-metHu-Leptin After Subcutaneous Injection to Sheep - Danielle N. McLennan; Christopher J. H. Porter; Glenn A. Edwards; Maria Brumm; Steven W. Martin; Susan A. Charman (Pharmaceutical Research, 2003)

Lymphatic Absorption Is a Significant Contributor to the Subcutaneous Bioavailability of Insulin in a Sheep Model - Susan A. Charman; Danielle N. McLennan; Glenn A. Edwards; Christopher J. H. Porter (Pharmaceutical Research, 2001)

Taurine indirectly increases [Ca]i by inducing Ca2+ influx through the Na+-Ca2+ exchanger - Ghassan Bkaily; Doris Jaalouk; Sawsan Sader; Hadia Shbaklo; Pierre Pothier; Danielle Jacques; Pedro D'Orléans-Juste; Edward J. Cragoe; forename Bose (Molecular and Cellular Biochemistry, 1998)